2011
DOI: 10.1021/ac201670e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Cellular Phenotypic Profiling: Prediction, Identification, and Analysis of Bioactive Natural Products

Abstract: Natural products have always been a major source of therapeutic agents; however, the development of traditional herbal products has been currently hampered by the lack of analytic methods suitable for both high-throughput screening and evaluating the mechanism of action. Cellular processes such as proliferation, apoptosis, and toxicity are well-orchestrated in real time. Monitoring these events and their perturbation by natural products can provide high-rich information about cell physiological relevancies bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Cell-based TCRP technology that evaluates multiple physiological changes would provide richer information about interactions between bacteria and hosts than endpoint assays [14], [41], [42]. However, the inherent variability and complexity of cells should be taken into full consideration in experimental design, implementation, and analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-based TCRP technology that evaluates multiple physiological changes would provide richer information about interactions between bacteria and hosts than endpoint assays [14], [41], [42]. However, the inherent variability and complexity of cells should be taken into full consideration in experimental design, implementation, and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inherent variability and complexity of cells should be taken into full consideration in experimental design, implementation, and analysis. Introduction of statistical model of TCRPs will address this problem [41]. In addition, because of the ability to measure over time and dosage, TCRP offers the possibility of using multiple variables in mathematic simulations for kinetic measurement of cell phenotypic changes.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular is to profile compound-induced cell signaling in confluent cells, given that the cells once reach confluency start to enter a new growth cycle or a quiescent state and the compound-induced response is almost exclusively due to cell signaling (Fang, 2010, 2011a). Alternatively, the long-term impacts of compounds on cell growth can also be used to screen compound library (Abassi et al, 2009; Fu et al, 2011). Of note, this approach may be able to identify ligands for other classes of targets such as nuclear receptors whose activation by themselves may not result in rapid signaling-related biosensor responses.…”
Section: Label-free Cell Phenotypic Screeningmentioning
confidence: 99%
“…The uses of multiple chemical markers such as nucleosides, ergosterol, mannitol and polysaccharides used for quality control also have some drawbacks (Li et al 2006a). Fu et al (2011) reported process for more precise authentication of sample continuous monitoring of cellular impedance in real time, which produces specific time/dose dependent cell response profiles (TCRPs) in addition to spectroscopic fingerprinting of active compounds by HPLC using adenosine (or 3-deoxyadenosine) as a standard, in accordance with Pharmacopoeia of the People's Republic of China (2005 version). The use of bar-coding and fingerprinting to some extent are in practice now-a-days with accession of ITS and 18s ribosomal RNA gene (MMDBD 2012).…”
Section: Dose and Toxicitymentioning
confidence: 99%